A meta-analysis of contagious caprine pleuropneumonia (CCPP) in Ethiopia - Asmare, K.; Abayneh, T.; Mekuria, S.; Ayelet, G.; Sibhat, B.; Skjerve, E.; Szonyi, Barbara; Wieland, Barbara (Elsevier, 2016)
This systematic literature review was initiated due to lack of comprehensive information on the status and distribution of contagious caprine pleuropneumonia (CCPP) in Ethiopia. The objectives of the review were thus to provide a pooled prevalence estimate of CCPP in the country and asses the level of in between study variance among the available reports. To this end manual and electronic search was conducted between 8th of January and 25th of June 2015. A total of twelve published articles and one MSc thesis was retrieved from19 initially identified studies. Twenty five animal level datasets were extracted at regional level considering some hypothesized predictors. The retrieved data were summarized in a meta-analytical approach. Accordingly, the pooled prevalence estimate of CCPP was 25.7% (95% CI:20.9,31.0).The inverse variance square (I2) that explains the variation in effect size attributed to reports true heterogeneity was 95.7%.The sub-group analysis was also computed for assumed predictors including, age, sex, type of study population, production systems and regional states. Among these predictors, study population type revealed statistically significant difference (P < 0.05). Accordingly, the prevalence estimate for samples collected at abattoir was 39.2%, while that of samples collected at field level was 22.4%. In the final model, type of study population fitted the multivariable meta-regression model accounting for 22.87% of the explainable proportion of heterogeneity among the presumed predictors. Evidence on isolation and confirmation of Mycoplasma capricolum sub spp capripneumonie in the country was obtained from five regional states. In conclusion, it is recommended to further investigate facilities related with transportation and collection premises along with potential role of sheep in the epidemiology of CCPP. Finally, the review emphasizes the need for monitoring the ongoing CCPP control intervention and introduces amendments based on the findings. Besides more surveys are needed in some of the regions where no or few valid data was available.